Czysto ludzka sprawa? Archeologiczne przywracanie pamięci o trudnej przeszłości przez tropienie naturo-kulturowych przemian cmentarzy wojennych - Zalewska, Anna; Cyngot, Dorota; Czarnecki, Jacek; Kiarszys, Grzegorz (Folia Praehistorica Posnaniensia, 2019)
In this article the outcomes of historical, archaeological, spatial and anthropological research concerning material remnants of the war cemeteries left by the Great War in Central Poland, in the area of Rawka and Bzura are presented. On the example of one of the four communes (Nowa Sucha) subjected to research under the project Archaeological Revival of Memory of the Great War (ARM), the processes of creation, transformation, decay, destruction and re-making present the resting places of the soldiers fallen between December 1914 and July 1915 are shown. In the first part, we sketch the output atmosphere that accompanied the primary context in which war cemeteries were established and place the war cemeteries in the network of social, formal and legal determinants. In the second part, we frame the historical and social contexts in which the resting places of the fallen soldiers of the German and Russian armies were massively created. Than, we show the difficulties associated with locating particular war cemeteries and signal strengths and obstacles in correlating results of archival research and use of remote sensing and archaeological methods in order to restore the memory of war cemeteries and establish their current and future condition as material warnings. Also we stress the looping of cultural and natural factors both in the process of protecting and destroying material condition of war cemeteries. Finally, on the example of one of the cemeteries we show how slow and arduous but at the same time promising can be the process of transformation from a forgotten/plowed cemetery into a place of/in memory, and as an agent struggling with the continuous nature-cultural transformations.